ANTIGENOTOXIC EFFECT FROM HERBAL TEA OF ELECAMPANE (INULA HELENIUM L.) ROOTS AND RHIZOMES (Experimental biology, 2016)
Genotoxic and antigenotoxic properties of herbal tea of Elecampane (Inula helenium L.) roots and rhizomes were studied. Using Comet assay method it was found that unsymmetrical dimethylhydrazine at a dose of 6.6 mg/kg caused DNA single-strand breaks in cells from different tissues of mice with frequency significantly exceeding the spontaneous level. Elecampane tincture at 600.0 mg/kg showed no mutagenic activity in laboratory animals, the frequency of DNA strand breaks was on the control level. But when combined with unsymmetrical dimethylhydrazine it substantially reduced mutagenic effect of the xenobiotic. Level of DNA strand breaks in cells of all the internal organs of mice was significantly decreased in a combined application of usymmetrical dimethylhydrazine with herbal tea. The results indicate the presence of antigenotoxic properties of herbal tea of elecampane roots and rhizomes.
Keywords: genotoxicity; antimutagen; Comet assay; rocket propellant; elecampane.